Pediatric heart failure - Kundan Mittal (Wolters Kluwer Medknow Publications, 2020)
The etiology of heart failure (HF) in children varies according to age, and congenital heart diseases are the most common cause of HF in pediatric population. HF must be differentiated from shock state. New-onset HF may be difficult to diagnose due to similarities in symptoms with respiratory and gastrointestinal diseases. Acute HF may be triggered by disturbance in preload, afterload, contractility, heart rate (HR), and diastolic functions, which contribute to cardiac output. The congestive state is treated using loop diuretics, and digitalis has little role in the management of pediatric HF.